Start here with Lotus 1-2-3 - Gasteiger, Daniel; Gasteiger, Daniel (New York : Bradbury Press, 1991)
Welcome to spreadsheet computing. Perhaps you want nothing to do with computers, but you have to learn about them for your job. Or, you might recognize that a computer can speed your work and have chosen this books to help you through your first sessions with Lotus 1-2-3. Whatever your orientation, there's a lot to learn. Before you begin, you should be convinced it be worth the effort.
Part I. Before You Start 1-2-3 -- Part II. Spreadsheets Basics -- Part III. Formulas and Functions -- Part IV. On the Way to Mastery.
Includes index.
Keywords: LOTUS 1-2-3 (COMPUTER FILE)